KONSELING RATIONAL EMOTIVE BEHAVIOR THERAPY UNTUK MENGUBAH POLA PERILAKU PADA REMAJA PELAKU PENGANIAYAAN - Rinna Yuanita Kasenda; Frauli Tatilu; Sharron Aurelia Mende (LPPM Universitas Cipta Mandiri, 2024)
This research aims to find out whether Rational Emotive Behavior Therapy counseling can change behavioral patterns in juvenile perpetrators of abuse in LPKA class 2 Tomohon. This study uses a qualitative method. The subjects of this research were teenagers who were involved in cases of peer abuse. The instruments that researchers use to collect and manage data are by using interview techniques and observing subjects. Researchers carried out interview and observation techniques by coming directly to the research site at LPKA class 2 Tomohon to obtain maximum data. The results found in this study indicate that after implementing therapy using the ABC theory in implementing the Rational Emotive Behavioral Therapy counseling approach, the researcher observed that the subject experienced changes and was able to differentiate between non-positive thoughts that had been stored and suppressed, thoughts or ideas. These ideas are compared with new thoughts conveyed and suggested by the counselor directly through real examples. Thus, this research is in line with previous research, namely REBT has the potential to change behavior patterns in adolescents, so the author draws the conclusion that REBT is able to change a person's behavior or thought patterns by making decisions in good conditions by thinking about the impact of the actions and behavior they carry out on their own thoughts